PEMANFAATAN QR CODE SEBAGAI MEDIA PEMBELAJARAN BERBASIS HISTORY DIGITAL DI MUSEUM SULAWESI TENGAH - Nur Jayanti, Ika; Mahmud Abdullah, Amira (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the utilization of QR Code as a digital history-based learning media to enhance interest in learning history at the Central Sulawesi Museum. The research method used is qualitative descriptive with data collection techniques including observation, interviews with museum staff and visitors consisting of teachers, lecturers, students, and documentation studies. The results show that QR Codes, implemented since 2023, facilitate quick and efficient access to historical collection information. Visitors feel more engaged and better understand the historical materials through this digital media, thereby increasing their learning interest. Although challenges such as limited digital literacy among some visitors and internet connectivity issues exist, the benefits of using QR Codes in supporting the learning process and preserving local culture are predominant. This study supports the importance of museum digitalization as a historical education strategy relevant to technological developments and the needs of the younger generation.